Anatomy, physiology and biomechanics of hamstrings injury in football and effective strength and flexibility exercises for its prevention - Zoric, I. (Journal of Human Sport & Exercise, 2012)
The muscles of the back of the thigh with its particular role in movement of athletes and people in general and, therefore, the position of the musculoskeletal system require specific attention in the athlete's training planned procession. As a group of muscles, which has an impact on two joint systems performs multiple missions, it is susceptible to various injuries. They act on the hip joints and knees, which are very important in basic movements of football players. Stabilizing role during movement requires very good coordination among these muscles with the synchronized activity of other muscles. Concentric and especially eccentric movements are very prominent during the movement of the hamstring muscles. Eccentric movements of the muscles lengthen muscle that is contracted and thus require much greater force activity that contributes to a risk of injury. Football as a complex activity has acyclic interval that requires a high degree of development of physical abilities in the modern sport but nobody paid attention to this muscle group. For this reason and many other factors, muscles of the back of the thigh have been frequently injured. Identifying all factors of risk, and trying to remove them is concern of many sports doctors, which is only possible with care and active participation of athletes themselves.